Peran Perlindungan Bagi Konsumen Dan Pelaku Usaha Berdasarkan Undang-Undang No. 8 Tahun 1999 - Yuliska, Edwin (Universitas Sumatera Barat, 2024)
Consumer protection is an important aspect in ensuring the creation of a balance between rights and obligations between consumers and business actors. Law no. 8 of 1999 concerning Consumer Protection aims to protect consumer rights from detrimental business practices, as well as encouraging the responsibility of business actors to run business ethically and in accordance with the law. This research aims to determine the importance of consumer protection in creating a fair relationship between consumers and business actors, as well as examining the effectiveness of implementing the Consumer Protection Law in Indonesia. This research uses a normative juridical method with a statutory approach related to regulations, doctrine, court decisions and other legal sources. The research results show that Law no. 8 of 1999 provides a strong legal basis for the protection of consumers and business actors. However, efforts are still needed to increase socialization, legal education for the community, and stricter law enforcement to encourage legal awareness for both consumers and business actors.